2017
DOI: 10.1002/anie.201703380
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Nickel‐Catalyzed Intramolecular Allylic Alkenylations Enabled by Reversible Alkenylnickel E/Z Isomerization

Abstract: Enantioselective nickel‐catalyzed arylative cyclizations of substrates containing a Z‐allylic phosphate tethered to an alkyne are described. These reactions give multisubstituted chiral aza‐ and carbocycles, and are initiated by the addition of an arylboronic acid to the alkyne, followed by cyclization of the resulting alkenylnickel species onto the allylic phosphate. The reversible E/Z isomerization of the alkenylnickel species is essential for the success of the reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 75 publications
4
44
0
Order By: Relevance
“…(18) In 2017, the Lam group reported enantioselective nickelcatalyzed intramolecular arylative allylic alkenylations, where the intermediate alkenylnickel species cyclizes onto a Z-allylic phosphate to give chiral 1,4-diene-containing hetero-and carbocycles (Table 7). [66] These reactions used (S)-t-Bu-NeoPHOX (L2) as the chiral ligand in TFE as the solvent, and excellent enantioselectivities were observed. Similar to cyclizations onto cyclohexa-2,5-dienones reported previously (Table 6), [65] small quantities of minor products 50 were observed in most of these reactions.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…(18) In 2017, the Lam group reported enantioselective nickelcatalyzed intramolecular arylative allylic alkenylations, where the intermediate alkenylnickel species cyclizes onto a Z-allylic phosphate to give chiral 1,4-diene-containing hetero-and carbocycles (Table 7). [66] These reactions used (S)-t-Bu-NeoPHOX (L2) as the chiral ligand in TFE as the solvent, and excellent enantioselectivities were observed. Similar to cyclizations onto cyclohexa-2,5-dienones reported previously (Table 6), [65] small quantities of minor products 50 were observed in most of these reactions.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…More recently, nickel catalysis has also been shown to be highly effective in these reactions. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] As well as being less expensive and more readily available than the more commonly used rhodium or palladium catalysts, nickel catalysis can offer unique possibilities in reaction development not readily available to these other catalyst systems. [76][77][78][79][80][81][82][83][84][85][86][87][88][89] This review will describe nickel-catalyzed arylative cyclizations of alkyne-and allene-tethered electrophiles using arylboron reagents, that proceed by the general mechanistic pathways shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Fletcher has introduced as et of efficient enantioselective reactions,c atalyzed by ab inap-Rh complex and involving racemic cyclic allylic chlorides and alkenyl boronic acids (Scheme 18). [41] 4.2.3. With asilyl-substituted propargyl boronate EAS with ap ropargyl moiety can be catalyzed by as ulfonate NHC-Cu complex.…”
Section: With Alkenyl Boronatesmentioning
confidence: 99%
“…Moreover, there are few asymmetric methods for the de novo construction of cyclopent‐2‐enones with a quaternary stereocenter at the 5‐position (as in 3 ) . Although our previous work on enantioselective nickel‐catalyzed arylative cyclizations of alkynyl electrophiles showed that ketones and activated alkenes, are competent reaction partners for alkenylnickel species, the ability of less electrophilic esters to undergo analogous cyclizations was less certain. Herein, we report the successful implementation of this strategy.…”
Section: Figurementioning
confidence: 99%